2013
DOI: 10.4103/1658-354x.109801
|View full text |Cite
|
Sign up to set email alerts
|

A randomized controlled trial to compare fentanyl-propofol and ketamine-propofol combination for procedural sedation and analgesia in laparoscopic tubal ligation

Abstract: Background:Procedural sedation and analgesia is widely being used for female laparoscopic sterilization using combinations of different drugs at varying doses. This study compared the combination of fentanyl and propofol, and ketamine and propofol in patients undergoing outpatient laparoscopic tubal ligation, with respect to their hemodynamic effects, postoperative recovery characteristics, duration of hospital stay, adverse effects, and patient comfort and acceptability.Settings and Design:Randomized, double … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
6
1

Year Published

2018
2018
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 9 publications
0
6
1
Order By: Relevance
“…They observed that mean blood pressure was consistently higher in the Ketamine group, as sympathomimetic effects of ketamine might have overcome the cardiovascular effects of propofol, thereby maintaining hemodynamic stability in these patients compared to the propofol-treated patients. In contrast with our findings, a study performed by Singh et al (10,11) comparing the cardiovascular effects of propofol alone and in combination with ketamine or fentanyl for sedation in patients undergoing endoscopic ultrasonography showed no significant differences in the mean blood pressure or heart rate at any time point among the groups. These conflicting results are probably related to the type of the procedures, as tubal ligation is a surgical operation, while endoscopy is a minimal invasive procedure (9).…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…They observed that mean blood pressure was consistently higher in the Ketamine group, as sympathomimetic effects of ketamine might have overcome the cardiovascular effects of propofol, thereby maintaining hemodynamic stability in these patients compared to the propofol-treated patients. In contrast with our findings, a study performed by Singh et al (10,11) comparing the cardiovascular effects of propofol alone and in combination with ketamine or fentanyl for sedation in patients undergoing endoscopic ultrasonography showed no significant differences in the mean blood pressure or heart rate at any time point among the groups. These conflicting results are probably related to the type of the procedures, as tubal ligation is a surgical operation, while endoscopy is a minimal invasive procedure (9).…”
Section: Discussioncontrasting
confidence: 99%
“…Although there was a higher incidence of nausea in the Ketofol group, there was no significant difference between the two groups in terms of the incidence and severity of nausea and vomiting in the present study. Inconsistent with this finding, another study comparing the administration of a bolus dose of ketofol, compared to fetofol (fentanyl + propofol) showed significantly higher severity of nausea in the ketofol group than in the Fetofol group (11).…”
Section: Discussionmentioning
confidence: 85%
“…9 Propofol and fentanyl combination has been used previously in laparoscopic ligation procedures both for anesthesia as well as for procedural sedation with local anaesthesia and has shown good intraoperative results as well as faster postoperative recovery. 10,11 Propofol in combination with ketamine has been used as procedural sedation during lap ligation and good intraoperative conditions have been obtained with some delay in recovery as compared to propofol fentanyl combination. 11 The pentazocine has been used as a procedural sedation with promethazine or diazepam for sedation and analgesia during dental or gynecological procedures.…”
Section: Discussionmentioning
confidence: 99%
“…10,11 Propofol in combination with ketamine has been used as procedural sedation during lap ligation and good intraoperative conditions have been obtained with some delay in recovery as compared to propofol fentanyl combination. 11 The pentazocine has been used as a procedural sedation with promethazine or diazepam for sedation and analgesia during dental or gynecological procedures. 12 However only two studies could be traced which involved ketamine plus pentazocine for sedation during procedures like abdominal tubectomy, D and C, D and E, I and D, removal of foreign bodies, excision of cysts and small tumors, eversion of sac, wound debridement and sequestrectomy and showed good results.…”
Section: Discussionmentioning
confidence: 99%
“…Fentanyl is a commonly used opioid that provide rapid onset, short duration potent analgesia, useful during anesthetic induction. Using Ketamine and Propofol in combination allows sedation to be achieved at lower total doses of each drug [5], using a combination of Ketamine and Propofol with several ration of 2:1, 1:1 or 1:5 has been reported in several studies [14] [15], Fentanyl and PROP has been efficiently used in separate syringes by Bajwa and his colleagues [16] another study reported their mixing in the same syringe [17] in several procedures. In our study, we used a simple and easy method to maintain the level of sedation by adding increments of bolus doses were used to maintain a steady state level of sedation.…”
Section: Discussionmentioning
confidence: 99%